Deaesthetic(s): a performance of and from a space of dislocation, a critical analysis of the violent aesthetic imprisonment(s) in/of knowledge production - Molale, Itumeleng (My University, 2020)
This thesis explores a theory I have developed called the Deaesthetic, which is a is a theory that makes three moves. 1)A refusal of the binary that opens a racial/gendered positionality, 2)refusal of the moment of deconstruction, 3)refusal of a moment of reconstruction in some recuperative way. The first move is the aesthetic written under erasure, which speaks to the ruse and collapse of a category of the aesthetic when thinking the black arts in its varied formations across the black diaspora. The second move is a refusal of any positionality that sees possibility in historically inherited modes of recognition when thinking knowledge quantificatio. Lastly the refusal of the deconstructivist moment of re-inscribing of bettered version of the old. Chapter one, are the iterations that foreground the entire research and helps frame how the subsequent chapters are read. Chapter two, Deaesthetic thinking with dislocation, employs a theory I am thinking of as “thinking beyond the wall” of the academic and cartographic specificity. This chapter addresses a dislocated non-position that creates a collage of “black studies” in all its varied articulations, from the South African, American and British canon in its trans-Atlantic configuration of Black thought. Chapter three is understood as a performance of and from a space of dislocation exploring the cartographic modes of containment that lead to the violent epistemes that create marginality of theories that become perceived as ‘other’. Here I think with dislocation as a mode that opens the unmappability of black thought that is presented by its trans-Atlantic collage. Chapter four focuses on the figure of man and knowledge and explores a critique of the euro-modern accumulation of the enlightenment and the category of man as the condition of knowledge production. The fifth and final chapter explores the core of my research which is framed from the performative moments in which I explore a writing through doing. This chapter is not an explanation of the theories it mobilises but points to the necessity of encountering the moments as moments of theory making within themselves. The chapter points to the performative and does not explain the performative moment
A dissertation submitted in accordance with the requirements for the degree of Master of Arts In Fine Arts, at the University of Witwatersrand, 2020